Market‐Based Incentives and Private Ownership of Wildlife to Remedy Shortfalls in Government Funding for Conservation. Issue 4 (13th October 2016) - Wilson, George R.; Hayward, Matt W.; Wilson, Charlie
Abstract: In some parts of the world, proprietorship, price incentives, and devolved responsibility for management, accompanied by effective regulation, have increased wildlife and protected habitats, particularly for iconic and valuable species. Elsewhere, market incentives are constrained by policies and laws, and in some places virtually prohibited. In Australia and New Zealand, micro economic reform has enhanced innovation and improved outcomes in many areas of the economy, but economic liberalism and competition are rarely applied to the management of wildlife. This policy perspective examines if commercial value and markets could attract private sector investment to compensate for Government underspend on biodiversity conservation. It proposes trials in which landholders, community groups, and investors would have a form of wildlife ownership by leasing animals on land outside protected areas. They would be able to acquire threatened species from locally overabundant populations, breed them, innovate, and assist further colonization/range expansion while making a profit from the increase. The role of government would be to regulate, as is appropriate in a mixed economy, rather than be the (sole) owner and manager of wildlife. Wide application of the trials would not answer all biodiversity‐loss problems, but it could assist in the restoration of degraded habitat and connectivity.